Control preventivo dinamico de sistemas de energia electrica usando redespacho de generacion y corte de carga - Minussi, C. R. [UNESP]; Righeto, L. F P [UNESP]; Lotufo, A. D P [UNESP] (My University, 1999)
A model for preventive control in electrical systems is presented, taking into account the dynamic aspects of the network. Among these aspects, the effects provoked by perturbations which cause oscillations in synchronous machine angles (transient stability), such as electric equipment outages and short circuits, are presented. The energy function is used to measure the stability of the system using a procedure defined as the security margin. The control actions employed are load shedding and generation reallocation. An application of the methodology to a system located in southern Brazil, which is composed of 10 synchronous machines, 45 busses, and 72 transmission lines. The results confirm the theoretical studies.
Dynamic security control of electrical energy systems by generation reallocation and load shedding
Keywords: Electric load shedding; Electric power generation; Electric power systems; System stability; Dynamic security control; Generation reallocation; Transient stability; Control systems